Juxtaposing The Territorial Integrity and Self-Determination Principles in Nagorno-Karabakh Dispute - I Gusti Ayu Khanaya Manohara; I Made Budi Arsika; I Made Sena Darmasetiyawan (Jambura Law Review, 2023)
The separation of the former Soviet Union resulted in non civic divorces; ethnic cleansing, massacres, a territorial dispute which the Nagorno-Karabakh dispute stands as an example of. This conflict has been going on for years and is constantly evolving and regularly flares up resulting in casualties. The differing accusation of Armenia and Azerbaijan regarding the issue of the Nagorno-Karabakh conflict create different dimensions of the parties. Armenia sees the settlement as in the framework of self-determination whereas Azerbaijan pertains to the principle of territorial integrity in which both are the basic principles of international law thus leading to confusion regarding the legal dimensions of the conflict. With the most recent aggression, it is paramount now more than ever to seek the best possible settlement to put an end to the dispute. Until recently, Armenia accepts a deal with Russia to surrender the disputed territory by withdrawing its army. The main objective of this article is to give a general assessment of the disputed principles in this case